2019
DOI: 10.1186/s13053-019-0118-4
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal carcinoma in the course of inflammatory bowel diseases

Abstract: Background Colorectal cancer (CRC) and inflammatory bowel disease (IBD) are the most prevalent diseases of the digestive system, and their association is unequivocal. A long-standing inflammatory process is one of the causes of sporadic as well as inherited cancers as it impacts on malignant transformation in a wide variety of neoplastic diseases, including colorectal cancer. Methods An extensive publication search was performed in Medline and PubMed database. The keywo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 71 publications
0
60
0
2
Order By: Relevance
“…Usually, chronic inflammation is followed by the generation of ROS/RNS that, in turn, provoke oxidative DNA damage and the impairment of DNA repair pathways, thus promoting cell transformation. For instance, patients with Crohn’s disease (CD) and chronic intestinal inflammation were reported to accumulate high levels of ROS/RSN in colonic mucosa, correlated with disease severity and colorectal cancer [ 143 , 144 ]. In asbestosis, inflammatory condition triggered by the exposure to asbestos, neutrophils and macrophages release ROS, increasing the level of oxidative DNA damage and causing malignant mesothelioma (MM) in tumor arising from mesothelial cells [ 93 , 94 , 95 , 145 ].…”
Section: Dna Damage and Inflammation: A Strong Interplaymentioning
confidence: 99%
“…Usually, chronic inflammation is followed by the generation of ROS/RNS that, in turn, provoke oxidative DNA damage and the impairment of DNA repair pathways, thus promoting cell transformation. For instance, patients with Crohn’s disease (CD) and chronic intestinal inflammation were reported to accumulate high levels of ROS/RSN in colonic mucosa, correlated with disease severity and colorectal cancer [ 143 , 144 ]. In asbestosis, inflammatory condition triggered by the exposure to asbestos, neutrophils and macrophages release ROS, increasing the level of oxidative DNA damage and causing malignant mesothelioma (MM) in tumor arising from mesothelial cells [ 93 , 94 , 95 , 145 ].…”
Section: Dna Damage and Inflammation: A Strong Interplaymentioning
confidence: 99%
“…Chronic inflammation has been found to play a key role in the progression of colon cancers. Numerous studies have shown that inflammatory bowel diseases (IBDs), including Crohn’s disease and ulcerative colitis (UC), are associated with the development and progression of CRC [ 4 , 5 , 6 ]. It has been reported that 25% of patients with IBD have colon cancer [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with inflammatory bowel disease are at a higher risk of developing colorectal cancer compared to the general population. Similar to colorectal cancer, the pathology of inflammatory bowel disease involves alterations in the microbiota and is also associated with anemia, with patients requiring iron therapy [132,133]. Human clinical studies investigating oral iron against intravenous iron therapy on the intestinal microbiota in patients with inflammatory bowel disease have been conducted by Lee et al They found that oral iron differentially altered both bacterial phylotypes and fecal metabolites compared to intravenous iron therapy notably leading to a decreased Faecalibacterium prausnitzii and Ruminococcus bromi abundance following oral iron therapy [122].…”
Section: Iron Supplementation Microbiota and Colorectal Cancermentioning
confidence: 99%
“…A decreased abundance of these bacteria in inflammatory bowel disease patients can, therefore, contribute to the pathogenesis of disease through contributing to inflammation [137]. As inflammatory bowel disease can be a premalignant condition, the microbial mechanisms underpinning the pathology of the condition may have a similarity to those in colorectal cancer [132]. Hence, the negative impact of oral iron therapy on the microbiota in inflammatory bowel disease may act as an indicator of the potential outcomes in colorectal cancer.…”
Section: Iron Supplementation Microbiota and Colorectal Cancermentioning
confidence: 99%